Urban Segregation and the Special Political Zone in Ahmedabad: An Emerging Paradigm for Religio-Political Violence - Arvind Rajagopal (South Asia Multidisciplinary Academic Journal)
In this paper I inquire into how the disposition of public spaces and informal oral communication, can together create a commonsense mobilizing support for spectacular events of violence. The built form of the city, urban planning and resulting forms of social segregation, and popular linguistic practices, can combine to instantiate new political formations such as what I am calling a Special Political Zone, where the form of rule exercised is both modern and democratic, but undercut through exceptions which a majority of citizens participate in reproducing, wittingly or unwittingly.1